2019
DOI: 10.5222/ankem.2019.102
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antibiotic resistance profile of Corynebacterium striatum strains isolated from clinical samples

Abstract: Corynebacterium striatum is a normal inhabitant of human skin and mucous membranes. However, it has recently been reported as the cause of invasive infections and outbreaks. In addition, multidrug resistance of the bacterium is a significant concern. In this study, we aimed to determine the antimicrobial resistance of C.striatum strains to contribute to empirical antibiotic usage protocols. A total of 235 C.striatum strains isolated from inpatients between January 2017-December 2018 were investigated retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
0
1
Order By: Relevance
“…It has also been reported that the tetA and tetB genes play a role in the tetracycline resistance of C. striatum strains and that the mechanism of resistance involves an active efflux pump [26,31]. Many recent studies have not reported resistance to vancomycin and linezolid [16,[23][24][25]. Similarly, in our study, all strains were susceptible to vancomycin and linezolid.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has also been reported that the tetA and tetB genes play a role in the tetracycline resistance of C. striatum strains and that the mechanism of resistance involves an active efflux pump [26,31]. Many recent studies have not reported resistance to vancomycin and linezolid [16,[23][24][25]. Similarly, in our study, all strains were susceptible to vancomycin and linezolid.…”
Section: Discussionsupporting
confidence: 79%
“…In earlier reports, C. striatum strains were susceptible to many antibiotics [21,22]. However, they have been reported to be multidrug-resistant in recent studies [16,[23][24][25]. In the present study, all the C. striatum strains were resistant to penicillin, cefotaxime, and ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 38%